Literature Review: Guava Leaves (Psidium Guajava) for Treating Diarrhea - Rohama, Rohama; Febriani, Agnesia; Khairunnisa, Aisya F.; Mawarid, M.T.F.; Deviani, Norma (PROMOTOR, 2024)
Diarrhea is a significant health problem, especially in developing countries. Guava leaves (Psidium guajava) have long been used in traditional medicine to treat diarrhea. This study aims to review the literature on the effectiveness of guava leaves in treating diarrhea by focusing on ten aspects: raw material name, raw material content, raw material composition, active substance content, efficacy claims, empirical data, raw material standardization, preclinical test, toxicity test, and clinical trial. The results of several studies show that guava leaves contain tannins, flavonoids, saponins, and essential oils that play a role in the antidiarrheal effect. Preclinical research shows a reduction in the frequency of bowel movements and an increase in stool consistency in animal models. Although empirical claims and preclinical trials support the use of guava leaves as a treatment for diarrhea, more research is still needed regarding the standardization of raw materials, toxicity tests, and clinical trials to ensure its overall efficacy and safety.